Teaching social responsibility and geographic literacy through a course on social vulnerability in disasters. Issue 1 (2nd January 2020) - Schumann, Ronald L.; Tunks, Jeanne L.
ABSTRACT: Social vulnerability describes human susceptibility to harm or loss from hazards; hence, understanding the human-environment interactions that underlie vulnerability is essential for aspiring emergency managers. Notably, however, pedagogical scholarship on social vulnerability remains scarce. To address this gap, this paper considers how an upper-division undergraduate course integrates a state-mandated social science objective (social responsibility). Next, it profiles a teaching intervention (the Signature Assignment Institute) aimed at improving alignment of student assignments with this objective. Empirical comparison of student assignments reveals a statistically significant improvement in quality post-intervention. Finally, the paper discusses social vulnerability's aptness for promoting geographic literacy and social responsibility across the curriculum. Resources to improve student learning outcomes are also identified.